How small amounts of Ge modify the formation pathways and crystallization of kesterites. Issue 3 (19th January 2018) - Giraldo, S.; Saucedo, E.; Neuschitzer, M.; Oliva, F.; Placidi, M.; Alcobé, X.; Izquierdo-Roca, V.; Kim, S.; Tampo, H.; Shibata, H.; Pérez-Rodríguez, A.; Pistor, P.
Abstract : A fundamental analysis of the impact of Ge on the synthesis of Cu2 ZnSnSe4 :Ge by a sequential process is presented, reporting the consequences on the absorber morphology and solar cell devices performance. Abstract : The inclusion of Ge into the synthesis of Cu2 ZnSn(S, Se)4 absorbers for kesterite solar cells has been proven to be a very efficient way to boost the device efficiency in a couple of recent publications. This highlights the importance to elucidate the mechanisms by which Ge improves the kesterite solar cells properties to such a large extent. In this contribution, we first show how controlling the position and thickness of a very thin (10–15 nm) layer of Ge greatly influences the crystallization of kesterite thin films prepared in a sequential process. Typically, Cu2 ZnSnSe4 (CZTSe) films form in a bi-layer structure with large grains in the upper region and small grains at the back. By introducing Ge nanolayers below our precursors, we observe that large CZTSe grains extending over the whole absorber thickness are formed. Additionally, we observe that Ge induces fundamental changes in the formation mechanism of the kesterite absorber. In a detailed analysis of the phase evolution with and without Ge, we combine the results of X-ray fluorescence, X-ray diffraction and Raman spectroscopy to demonstrate how the Ge influences the preferred reaction scheme during the selenization. We reveal that the presence of Ge causes a large change in the in-depth elemental distribution, induces a stabilizing Cu–Sn intermixing, and thus prevents drastic compositional fluctuations during the annealing process. This finally leads to a change from a tri-molecular towards, mainly, a bi-molecular CZTSe formation mechanism. Kesterite thin films with surprisingly large crystals of several microns in diameter can be fabricated using this approach. The results are related to the increase in device performance, where power conversion efficiencies of up to 11.8% were obtained. Finally, the consequences of the disclosed crystallization pathways and the extension to other chalcogenide technologies are discussed.